Uso de los medios telemáticos en materia penal y su adecuación a las garantías del debido proceso - Acosta Pozo, Virginia Mercedes (2022)
This work will be the one that will lead to graduation as a lawyer, in this sense we chose to investigate by virtue of such a great goal, a topic that is being widely used as much as currently being questioned in Ecuadorian judicial practice from various points of view, as well as, with the topic: "Use of telematic means in criminal matters and their adaptation to the guarantees of due process", and through historical, deductive, inductive, bibliographic review methods, this investigation has been conducted in order to determine how general objective: Analyze how the correct application of telematic means in the judicial stage of the criminal process will fully guarantee the due process enshrined in the Constitution. Being able, after the analysis carried out, to arrive at a proposal that proposes from various angles the care of certain ignored or underestimated issues within the telematic hearings whose violation results in turn, in serious violations of due process.......